DECLARATION ON HEALTH IN SOUTHERN AFRICA MAPUTO, 15 APRIL 1990 - Conference Organising Groups (PINS-Psychology in Society, 2025)
This Maputo Conference - an International Conference on Health in Southern Africa - held between April 9-15 1990, has been a unique and unprecedented event at a moment of historic opportunity for the liberation struggle. This meeting has had a special and remarkable character for three reasons. It has brought together for the first time health and social welfare workers, anti-apartheid organisations representing more than 54 000 health workers from within South Africa, and their counterparts and comrades from the ANC, Mozambique and all of the Frontline States. It has addressed the urgent challenge, in this final and decisive stage of the liberation struggle, of formulating specific proposals, strategies and policies for the structure, organisation, financing and development of health and welfare services for a truly democratic South Africa. Of further political significance, the Maputo Conference has been an expression of the Mozambique government’s solidarity with progressive forces in South Africa, and a recognition of our shared experience of the tyranny of apartheid and our mutual abhorrence of the deliberate destabilisation of Mozambique, and in particular of the appalling atrocities perpetrated by the apartheid regime. This shared experience - including the deliberate apartheid effort, both within and outside South Africa. to destroy the potential for full development of entire generations - united us as brothers and sisters.